2006
DOI: 10.2981/0909-6396(2006)12[331:chatom]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Colonization history and taxonomy of moose Alces alces in southeastern Alaska inferred from mtDNA variation

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…, 2003; lichen Lobaria pulmonaria , Walser et al. , 2005; moose Alces alces , Hundertmark et al. , 2006; lodgepole pine Pinus contorta , Godbout et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 2003; lichen Lobaria pulmonaria , Walser et al. , 2005; moose Alces alces , Hundertmark et al. , 2006; lodgepole pine Pinus contorta , Godbout et al.…”
Section: Discussionmentioning
confidence: 99%
“…Moose have been present in Alaska since mid-to late-Pleistocene times (11,000-14,000 years BP) (Hundertmark et al 2003(Hundertmark et al , 2006. They likely survived in relatively small disjunct groups wherever suitable habitat could be found throughout this period, when a tundra-steppe community dominated much of Alaska refugia (LeResche et al 1974).…”
Section: Moose: Current and Historical Distributionmentioning
confidence: 99%
“…With the close of the glacial period and proliferation of shrub and forest communities, moose spread via river valleys throughout 90 percent of contemporary Alaska (LeResche et al 1974. Very recent extensions of moose distribution have occurred in the geographic extremes of Alaska; most relevantly in southeast Alaska, where glacial recessions have allowed moose to colonize coastal forests (Darimont et al 2005, Hundertmark et al 2006, Klein 1965, LeResche et al 1974 as well as by deliberate translocations to the Copper River Delta near Cordova (Paul 2009). LeResche et al (1974) concluded that, in most of Alaska, moose numbers have varied dramatically in local areas over the past two centuries, largely in response to fire and subsequent forest succession.…”
Section: Moose: Current and Historical Distributionmentioning
confidence: 99%
See 2 more Smart Citations